Intelligent, secure, and dependable systems in distributed and cloud environments : first International Conference, ISDDC 2017, Vancouver, BC, Canada, October 26-28, 2017, proceedings /: first International Conference, ISDDC 2017, Vancouver, BC, Canada, October 26-28, 2017, proceedings. (2017) - Unknown
No abstract available